Adesyvas Mikalojaus Daukšos Postilėje - Žilinskaitė, Eglė (Baltistica, 2007)
THE USE OF THE ADESSIVE CASE IN MIKALOJUS DAUKŠA’S POSTILLAThe local meanings of the adessive in Daukša’s Postilla are discussed. In other Old Lithuanian writings (Chylinskis’ translation of the New Testament, the Gospel of Luke from Bretkūnas’ translation of the Bible) the adessive is not used in its etymological meaning ‘position near to the object’, while in DP a 6,43% of the occurrences of the adessive are clearly used in its primary meaning.The use of the adessive is mostly associated with animacy. Adessives are described according to the animacy hierarchy and compared to Kavaliūnaitė’s analyses of the adessive in Chylinskis’ translation of the New Testament. In DP the usage of the adessive doesn’t follow the animacy hierarchy as closely as in Chylinskis’ text. In the 3rd person personal pronoun, in demonstrative pronouns, proper names, and common animate nouns denoting humans the adessive and the inessive cases are neutralized in the meanings ‘cognitive states and processes’ and ‘place among people’, while in Chylinskis the adessive and the inessive are in complementary distribution.
Keywords: senieji raštai; adesyvas; M. Daukša